ASSESSING READING ANXIETIES AMONG STUDENTS IN THE NIGER DELTA REGION (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
This study aims to identify reading anxiety among secondary school students. The research design employed a quantitative approach in  the form  of  a survey  study.  There  were  80 respondents who were willing to participate in this study. The respondents were students from one of secondary in the Niger Delta Region.     All  respondents  were  students  from junior secondary school classes.  To  collect  the  data,  this  study   adapted  a questionnaire from Ahmad et.al. (2013) which consists of five domains  of  reading  anxiety,  i.e.,  (1)  lack  of  vocabulary,  (2) unfamiliar topic,  (3)  unfamiliar  culture,  (4)  afraid  of  making errors, and (5) worry about reading effects. Based on the results, the statement with the highest score is “I enjoy reading a text in English text in English when I know its translation” (M=4.15; SD=.730). Meanwhile, the statement with the lowest score is “In reading aloud in the class I do not understand the text even though it is easy” (M=3.00; SD=1.055). The data imply that the most significant factor in students’ reading anxiety is lack of vocabulary  and  the  least  factor  is  worrying  about  reading effects.